Biomimetic ketone reduction by disulfide radical anion - Barata Vallejo, Sebastian (2021)
The conversion of ribonucleosides to 2′-deoxyribonucleosides is catalyzed by ribonucleoside reductase enzymes in nature. One of the key steps in this complex radical mechanism is the reduction of the 3′-ketodeoxynucleotide by a pair of cysteine residues, providing the electrons via a disulfide radical anion (RSSR•−) in the active site of the enzyme. In the present study, the bioinspired conversion of ketones to corresponding alcohols was achieved by the intermediacy of disulfide radical anion of cysteine (CysSSCys)•− in water. High concentration of cysteine and pH 10.6 are necessary for high-yielding reactions. The photoinitiated radical chain reaction includes the one-electron reduction of carbonyl moiety by disulfide radical anion, protonation of the resulting ketyl radical anion by water, and H-atom abstraction from CysSH. The (CysSSCys)•− transient species generated by ionizing radiation in aqueous solutions allowed the measurement of kinetic data with ketones by pulse radiolysis. By measuring the rate of the decay of (CysSSCys)•− at λmax = 420 nm at various concentrations of ketones, we found the rate constants of three cyclic ketones to be in the range of 104–105 M−1s−1 at ~22◦C.